2016
DOI: 10.1007/s00421-016-3362-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of muscle length on voluntary activation of the plantar flexors in boys and men

Abstract: The VA partly accounts for the plantar-flexors MVC torque difference between children and adults but is not affected by the muscle length changes in both groups. Therefore, VA cannot account for the shape of the torque-angle relationship on the plantar-flexor muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…For this normalization procedure to be correct, it is important that the maximal voluntary activation can be reached at every tested ankle angle. In this way, a recent study reported no changes in maximal voluntary activation level from 20 deg in plantarflexion to 10 deg in dorsiflexion (Kluka et al, 2016). It is therefore unlikely that the normalization procedure influenced the RMS EMG results obtained in the present study.…”
Section: Methodological Considerationssupporting
confidence: 42%
“…For this normalization procedure to be correct, it is important that the maximal voluntary activation can be reached at every tested ankle angle. In this way, a recent study reported no changes in maximal voluntary activation level from 20 deg in plantarflexion to 10 deg in dorsiflexion (Kluka et al, 2016). It is therefore unlikely that the normalization procedure influenced the RMS EMG results obtained in the present study.…”
Section: Methodological Considerationssupporting
confidence: 42%
“…), as well as higher plantar flexor activation at lengthening positions (Kluka et al . ) or no differences for joint angles (Papaiordanidou et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the testing procedure, the optimal stimulation intensities were determined from recruitment curves [the intensities where Qtwunpot and concomitant M-wave amplitudes of the KE muscles, i.e., vastus lateralis (VL), vastus medialis (VM), and rectus femoris (RF), and PF muscles, i.e., soleus (SOL) and gastrocnemius medialis (GM), reached their maximal values and started to plateau)]. The criterion to determine that the twitch and M-wave amplitudes reached a plateau was no further increase of these amplitudes, despite the increase of the stimulation intensity (22). The intensity where SOL H-reflex amplitude was maximal (I Hmax) (only for the PF muscles testing) was also determined from its recruitment curve.…”
Section: Subjectsmentioning
confidence: 99%
“…Interestingly, prepubertal children may have a greater percentage of slow-twitch muscle fibers in vastus lateralis (25) and a lower absolute force level of the KE muscles than adults (38). However, the differences in the absolute force level (22) and slow-twitch fiber proportion (13) between these two age groups could be reduced on the PF muscles. This could reduce the fatigue differences at peripheral and neural levels between children and adults on the PF muscles as compared with the KE muscles.…”
Section: Introductionmentioning
confidence: 99%